Acute effects of supplemental oxygen therapy using different nasal cannulas on walking capacity in patients with idiopathic pulmonary fibrosis: a randomised crossover trial. Issue 3 (17th August 2020) - Schneeberger, Tessa; Leitl, Daniela; Gloeckl, Rainer; Jarosch, Inga; Reimann, Daniela; Hitzl, Wolfgang; Koczulla, Rembert; Kenn, Klaus
Patients with idiopathic pulmonary fibrosis (IPF) and concurrent hypoxaemia should be treated with oxygen therapy [1]. Oxygen therapy is commonly given by conventional nasal cannulas (CNC), but can also be delivered by other less conventional cannulas such as the Oxymizer. The Oxymizer is a nasal cannula with an internal pendant reservoir incorporated in the lumen at the patient end which has the potential to provide increased oxygenation while using the same oxygen setting as one would with CNC [2]. Something simple, like changing a nasal cannula for a technologically superior one, can improve exercise capacity and oxygenation in patients with IPF. There is a need to develop improved cannulas for comfort and patient acceptance. https://bit.ly/2NelacE